PROTECTION OF RIGHTS OF NATURE AND THE POST-DEVELOPMENT PERSPECTIVE - Santiago, Mariana Ribeiro; Silva, Renata Cristina Oliveira Alencar (Revista Brasileira de Direito Animal, 2021)
The present study aimed to analyze the relationship between the protection of the rights of nature, especially animals, and economic development. For its elaboration, bibliographical searches were made by printed and electronic means, as well as analysis of judicial decisions and comparative law. After studying the collected material, it was possible to verify that the Kantian concept of dignity has been modified, opening space for an ecological dimension of human dignity. Also, it demonstrated that man has to be in his real position within the Earth ecosystem, which is on the same level as other non-human beings. Finally, it was concluded that economic development, for it to be truly sustainable, must be associated with respect for the rights of Nature, including the rights of animals, guaranteeing the preservation of the planet and all the beings that live on it.